A Novel Antimicrobial Peptides From Pine Needles of Pinus densiflora Sieb. et Zucc. Against Foodborne Bacteria - Lee, Junho; Kang, Hee Kyoung; Cheong, Hyeonsook; Park, Yoonkyung (Frontiers in Microbiology, 2021)
Pine needle is a traditional medicine used in several East Asian countries. It contains functional components that exhibit a wide spectrum of biological effects such as antioxidant and antimicrobial activities. We determined the antimicrobial activity of novel peptides isolated from Pinus densiflora Sieb. et Zucc. The four active pine-needle (PN) peptides showed potent antimicrobial activity against foodborne bacteria with minimum inhibitory concentration values ranged from 8 and 128 μg/mL. PN peptides showed no detectable hemolytic activity or cytotoxicity at the antimicrobial concentrations. The PN5 N-terminal amino acid sequence was identified using Edman degradation and BLAST homology analysis showed that it was not identical to any other protein. This suggests that PN5 can serve as an antimicrobial agent to be used as a preservative in the food industry.